Design of triple cogeneration system for hydrogen fuel cell in greenhouse based on resource analysis - Yang, Jinlong; Li, Rui; Lee, Chul-Hee (Frontiers in Energy Research, 2023)
Hydrogen energy has a massive advantage in the energy supply mode regarding greenhouse gas emissions. Nevertheless, the energy supply system needs to be redesigned to meet the heating/cooling needs and the goals of using hydrogen energy. The comprehensive utilization efficiency of system energy can be improved using resource analysis to solve the problem of waste heat and formulate a technical plan for triple cogeneration of hydrogen greenhouse. Compared to the coal boiler heating system and the hydrogen energy heating system, the advantages of the hydrogen greenhouse triple cogeneration system are that the comprehensive utilization efficiency of the system energy has been improved, and no CO2 is generated, which does not cause pressure on environmental protection. Currently, the economic advantages are not outstanding. Still, coal energy is expected to be replaced in the future with the continuous decline in the cost of hydrogen and fuel cells. The hydrogen greenhouse triple cogeneration system has considerable advantages in system energy efficiency and environmental attributes. The economic attributes will play a role in the future.